STUDENT WORKSHEET (LEMBAR KERJA PESERTA DIDIK/LKPD) TO TEACH READING FOR EIGHTH GRADE STUDENTS AT STATE JUNIOR HIGH SCHOOL (SMPN) 22 JAMBI CITY - Titis Eka Rahayu; Tartila (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2023)
This study aimed to design LKPD for eighth-grade students at SMPN 22 Jambi City. This study employed a Research and Development (R&D) design. This study produced an LKPD for the reading skill of eighth-grade students. The process of designing the LKPD employed the ADDIE model: Analysis, Design, Develop, Implementation, and Evaluation. A material expert and a design expert validated the LKPD. After the experts validated the LKPD, the teacher also assessed it. After the product was validated and revised, it was given to students to know their responses to using the LKPD. This product has obtained a validity score of 89,23% from the material expert and 91,67% from the design expert. The validation score from the teacher was 94,67%. A score of 89% was obtained from the students’ responses. It means that the LKPD was accepted as an instructional medium to teach reading.